2001
DOI: 10.1523/jneurosci.21-14-05251.2001
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Integration of Whisker Information in the Primary Somatosensory Cortex of Rats

Abstract: The isomorphic representation of the contralateral whisker pad in the rodent cerebral cortex has served as a canonical example in primary somatosensory areas that the contralateral body surface is spatially represented as a topographic map. By characterizing responses evoked by multiwhisker stimuli, we provide direct evidence that the whisker region of the rat primary somatosensory cortex (SI) integrates information from both contralateral and ipsilateral whisker pads. The proportions of SI neurons responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
129
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 37 publications
23
129
0
Order By: Relevance
“…In the rodent, it has been observed that deflection of ipsilateral whiskers suppresses cortical responses evoked by contralateral whisker stimulation (Shuler et al, 2001), consistent with other anatomical (Carr and Sesack, 1998) and electrophysiological (Kawaguchi, 1992) evidence supporting the conclusion that, under normal conditions, callosal inputs have a net inhibitory influence.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the rodent, it has been observed that deflection of ipsilateral whiskers suppresses cortical responses evoked by contralateral whisker stimulation (Shuler et al, 2001), consistent with other anatomical (Carr and Sesack, 1998) and electrophysiological (Kawaguchi, 1992) evidence supporting the conclusion that, under normal conditions, callosal inputs have a net inhibitory influence.…”
Section: Introductionsupporting
confidence: 77%
“…Although transection of the corpus callosum, the main anatomical structure that connects the two cortical hemispheres, results in only subtle sensory and motor deficits (Gazzaniga, 2000), many studies have confirmed that cortical neuron responses can be strongly influenced by activation of peripheral ipsilateral inputs (Armstrong-James and George, 1988;Clarey et al, 1996;Shuler et al, 2001Shuler et al, , 2002Pluto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SII fields are connected by callosal fibers, and their role may not be simply combining excitatory signals of two hemispheres to yield bilateral receptive fields. Experiments using denervation or reversible inactivation have attributed transcallosal activity a modulatory role in bilateral interactions (Shuler et al, 2001). In addition to the direct callosal projection, SII and SI fields in the two hemispheres can also interact via fibers descending to the thalamus (Raij et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interhemispheric connections between the barrel fields were described by Olavarria et al (1984) and Koralek et al (1990) in the rat, who found that they are confined to the septal regions. The work on unanesthetized rats by Shuler et al (2001) and Wiest et al (2010) found a proportion of units that responded to stimulation of vibrissae from either side of the muzzle in layer V of the barrel cortex. Bilateral subthreshold receptive fields were also described in that layer by Manns et al (2004).…”
Section: Discussionmentioning
confidence: 99%